The Origins and Historical Assembly of the Brazilian Caatinga Seasonally Dry Tropical Forests - Fernandes, Moabe F.; Cardoso, Domingos; Pennington, R. Toby; de Queiroz, Luciano P. (Frontiers in Ecology and Evolution, 2022)
The Brazilian Caatinga is considered the richest nucleus of the Seasonally Dry Tropical Forests (SDTF) in the Neotropics, also exhibiting high levels of endemism, but the timing of origin and the evolutionary causes of its plant diversification are still poorly understood. In this study, we integrate comprehensive sampled dated molecular phylogenies of multiple flowering plant groups and estimations of ancestral areas to elucidate the forces driving diversification and historical assembly in the Caatinga flowering plants. Our results show a pervasive floristic exchange between Caatinga and other neotropical regions, particularly those adjacent. While some Caatinga lineages arose in the Eocene/Oligocene, most dry-adapted endemic plant lineages found in region emerged from the middle to late Miocene until the Pleistocene, indicating that only during this period the Caatinga started to coalesce into a SDTF like we see today. Our findings are temporally congruent with global and regional aridification events and extensive denudation of thick layers of sediments in NE Brazil. We hypothesize that global aridification processes have played important role in the ancient plant assembly and long-term Caatinga SDTF biome stability, whereas climate-induced vegetation shifts, as well as the newly opened habitats have largely contributed as drivers of in situ diversification in the region. Patterns of phylogenetic relatedness of Caatinga endemic clades revealed that much modern species diversity has originated in situ and likely evolved via recent (Pliocene/Pleistocene) ecological specialization triggered by increased environmental heterogeneity and the exhumation of edaphically disparate substrates. The continuous assembly of dry-adapted flora of the Caatinga has been complex, adding to growing evidence that the origins and historical assembly of the distinct SDTF patches are idiosyncratic across the Neotropics, driven not just by continental-scale processes but also by unique features of regional-scale geological history.